AUDITING OF EUROPEAN FUNDED PROJECTS - Niculina, STANESCU (Strategii Manageriale, 2014)
A mission on the European funded projects performed by the financial auditor consists in the complete checking of the amounts requested for reimbursement by the beneficiary in the Reimbursement/payment application of the costs for the action financed in compliance with the terms and conditions of the financing contract, fitting the project budget into the sums planned, verifying the registration in the bookkeeping, the reconciliation of the accounts, the drafting of the expenditure and the submission of the report of the factual findings to the beneficiary on the agreed procedures applied. Thus the checking of the expenditure is done by the auditor in terms of reality, legality, accuracy and eligibility.